Efek Memediasi Pengembangan Karir pada Pengaruh Pelatihan terhadap Kinerja Pegawai - Syahputra, Sandi Mulia; Chairunnisa, Lyza Tahura; Putra, Rizky (Universitas Harapan Medan, 2024)
This study aims to analyzed the effected of mediating career development in the effected of training toward on employee performance at Dinas Koperasi dan UKM. This research was conducted at Dinas Koperasi dan UKM. In this study the population were employees who worked in Dinas Kiperasi dan UKM which consists of 7 divisions with a total of 165 employees, the sample was taken using a census sample so that the total sample was 165 respondents. Sources of data using primary data with data collection techniques, namely questionnaires. The data analysis technique used path analysis test, data validity and quality test, classical assumption test and hypothesis test. Based on the results of the study, it showed that partially training has significant effected toward career development, training has significant effectedtoward employee performance, and career development has significant effectedtoward employee performance in Dinas Koperasi dan UKM. Simultaneously, training and career development together have significant effectedtoward employee performance, career development mediated the effected of training toward employee performance in Dinas Koperasi dan UKM